ANALISIS PERAN KELOMPOK WANITA TANI (KWT) TERHADAP PENINGKATAN EKONOMI KELUARGA DI KECAMATAN SIMPUR KABUPATEN HULU SUNGAI SELATAN - Fauziah, Ririn; Ratumbuysang, Monry Fraick Nicky Gillian; Rizky, Maulana; Nor, Baseran (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to determine the influence of the role of women farmer groups (KWT) on improving the family economy in Simpur District, Hulu Sungai Selatan Regency. The population used in this research were KWT members in Simpur District, HSS Regency. There were 11 KWTs spread throughout the villages of Simpur District. The sampling method is using non-probability sampling technique. The type of nonprobability sampling used is purposive sampling. The purposive sampling method obtained 70 samples. The data analysis technique uses SMART PLS. The research results found that there was a positive and significant influence between the role of KWT on improving the family economy in Simpur District, HSS Regency.